AI-Powered Smart and Personalized Education Platform - V, Dunusinghe A.; A, Ranasinghe T. K. S.; H, Gamage J. G. A. C.; T, Perera K. G. D.; Thelijjagoda, Samantha; Gunatilake, Poojani (2023 International Conference on Innovative Computing, Intelligent Communication and Smart Electrical Systems (ICSES), 2023)
An AI assistant addresses online education's shortcomings, focusing on personalized learning and career guidance. It provides tailored recommendations, assesses performance, suggests subjects, and crafts learning plans. Objectives include accurate grade prediction, subject stream advice, customized assessments, and personalized strategies. The study shows data analytics and machine learning forecast grades, while multi-tenancy architecture improves data handling. Personalized assessments consider both academics and soft skills. Machine learning promises accurate subject stream predictions, and engagement detection aids in optimal learning. This AI system holds potential in reshaping online education, but ongoing improvements are vital for enhanced learning.